AB0563 Takayasu's Arteritis: Experience from A Tertiary Care Centre in Western India. (15th July 2016) - Sagdeo, P.S.; Samant, R.; Balakrishnan, C.; Mangat, G.; Parikh, T.; Gc, Y.
Abstract : Background: Takayasu's arteritis (TA) is a rare, granulomatous panarteritis of aorta and its major branches, most commonly presenting before the age of 40 years. There is limited data regarding epidemiology of TA from India. Objectives: To describe the clinical profile and outcome of patients with Takayasu arteritis from a tertiary care centre in western India. Methods: We analysed medical records of TA patients satisfying the 1990 Criteria of American College of Rheumatology for the Classification of Takayasu Arteritis attending Rheumatology Department from 2009 to 2014.Demographic, clinical, laboratory, imaging features and intervention done were noted. Results: Forty Eight patients were included. Mean ESR at first visit of patients was 51mm/hr and last visit was 28 mm/hr. Mean ITAS at first visit was 10.9 and last visit was 0.6.CT angiography was used in 41%, PET was done in 70% and repeat PET was done in 35%. Conclusions: 1. 12 (25%) patients were diagnosed in pre pulseless stage of disease. 2. As per angiographic classification class V disease was most common seen in our cohort. 3. 27% patients were refractory to treatment requiring surgical intervention. References: Jain, S., Kumari, S., Ganguly, N. K. & Sharma, B. K. Current status of Takayasu arteritis in India. Int. J. Cardiol.1996; 54 (Suppl.):S111-S116 Arend, W P; Michel, B A; Bloch, D A; Hunder, G G; Calabrese, L H et al. The American College of Rheumatology 1990 criteria for the classification of Takayasu arteritis. Arthritis and rheumatism 1990 vol. 33 (8) p. 1129–34 Disclosure of Interest: None declared